ANALISIS SENSITIVITAS HARGA OPSI MENGGUNAKAN METODE GREEK BLACK SCHOLES - NANDITA. N, DEVI; DHARMAWAN, KOMANG; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Vol 7 No 2 (2018)DO - 10.24843/MTK.2018.v07.i02.p197, 2018)
Sensitivity analysis can be used to carry out hedging strategies. The sensitivity value measures how much the price change of the option influenced by some parameters. The aim of this study is to determine the sensitivity analysis of the buying price of European option by using the Greek method on Black Scholes Formula. From this study we get the values of delta, gamma, theta, vega, and rho. The values of deltas, gamma, vega, and rho are positive, which means that the value of the option is more sensitive than the corresponding parameter. The most sensitive value of gamma is obtained when the stock price approaches the strike price and approaches the expiry date. The value of theta obtained is negative and hence the most sensitive theta value is when the value is getting smaller. While, the most sensitive value of vega is obtained when the stock price is close to the strike price and is far from the expiry date. The most sensitive value of rho is obtained when the stock price gets bigger and farther from the expiry date.